Molecular identification of drug resistant mutations to tetracycline in Mycoplasma spp. isolated from patients with multiple sclerosis - Naghib, M.; Kheirkhah, B.; Mohebbi, R.; Sadeg, L. (Cellular and Molecular Biology, 2017)
Bacterial infections play a significant role in causing or intensifying the attacks in MS and there are reports based on the interference of Mycoplasma with a global distribution. Mycoplasma causes autoimmune attacks by imitating the host cell membrane, which is a way of resistance to antibiotics. The purpose of this study was to evaluate the molecular identification of mutations causing resistance to tetracycline in Mycoplasma isolated from MS patients. A total number of 32 cerebrospinal fluid samples and 48 urinal fluid samples were collected from MS patients. The samples were enriched in 7 PPLO broth for one night and continuous cultivation in agar PPLO and PPLO broth for one week. DNA was extracted, and then nested PCR and Doublex PCR were used for bacteria genus identification and the presence of potential tetracycline-resistant alleles (rrs4 and rrs3), respectively. A total number of 12 samples created colonies. However, only 5 samples (1 cerebrospinal fluid and 4 urinal samples) were detected to be Mycoplasma. The urinal samples showed the desired alleles and were tetracycline-resistant. By sequencing the PCR products, it was shown that these alleles have mutated in various points. Based on the results it seems that the resistant mutated Mycoplasma can be detected in MS patients in our population and may be considered as a risk factor for the disease.